ETHOLOGICAL MECHANISMS OF THE MAINTENANCE OF COAT COLOR POLYMORPHISM IN THE POPULATION OF THE NORTHERN RED-BACKED VOLE (MYODES RUTILUS) ROUND NOVOSIBIRSK - O. F. Potapova; M. A. Potapov; V. V. Panov; V. I. Evsikov (Вавиловский журнал генетики и селекции)
The population of the Northern red-backed vole (Myodes rutilus) from the vicinity of Novosibirsk is polymorphic for coat coloration. Some of its individuals possess an unusual black color of rump. Experimental studies have shown that mature males with the aberrant coloration outperform standard males in such adaptive characteristics as body mass and exploratory activity, rank higher in social hierarchy, have an optimal balance between amicability and aggressiveness, and are more attractive for receptive females. All these features give the aberrant males an advantage at high population density and intensity of social competition as early as the beginning of the mating season. As a result, they produce more offspring, and the proportion of the aberrant individuals increases. However, the early-born aberrant progeny also early matures and starts its reproduction, thus, it is eliminated in the autumn. In a sparser population, the aforementioned advantages are less significant, and the proportion of the aberrant form remains unchanged by the end of the reproductive season. Thus, the ethological mechanisms determining male competitive capacity and female mating preferences contribute in the maintenance of the dynamic coat-color polymorphism in the Northern red-backed vole population.